The Influence Of Fundamental Analysis, Technical Analysis And Broker Analysts In Bursa Malaysia - Chee, Wern Wye (2008)
This paper examined the presence of fundamental analysis, technical analysis and broker analyst in influencing the investment decision among investors in Bursa Malaysia.